2017
DOI: 10.1093/jac/dkw558
|View full text |Cite
|
Sign up to set email alerts
|

Pan-azole-resistantCandida tropicaliscarrying homozygouserg11mutations at position K143R: a new emerging superbug?

Abstract: A novel point mutation (K143R) located in the erg11 gene of C. tropicalis was found in pan-azole-resistant strains. According to our protein homology model, it is very likely that the mutation K143R causes pan-azole resistance in C. tropicalis . Moreover, an up-regulation of ABC transporters was observed, which can add up to a pan-azole-resistant phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
19
0
3
Order By: Relevance
“…Studies have demonstrated that Erg11p amino acid substitutions in the 14α-sterol demethylase involved in the biosynthesis of sterol ergosterol results in decreased fluconazole susceptibility in C. tropicalis clinical isolates [ 9 , 20 , 21 ]. Jiang et al demonstrated that two mutations, Y132F and S154F, are responsible for azole resistance by inserting them into wild-type isolate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that Erg11p amino acid substitutions in the 14α-sterol demethylase involved in the biosynthesis of sterol ergosterol results in decreased fluconazole susceptibility in C. tropicalis clinical isolates [ 9 , 20 , 21 ]. Jiang et al demonstrated that two mutations, Y132F and S154F, are responsible for azole resistance by inserting them into wild-type isolate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These expression studies were later verified through direct expression in C. albicans ( 11 ). The equivalent Y132F and/or K143R substitutions were also associated with azole resistance in Candida tropicalis ( 12 14 ), Candida parapsilosis ( 15 , 16 ), and Candida orthopsilosis ( 17 ). Residues Tyr132 and Lys143 lie within the substrate binding pocket of the Erg11 protein (lanosterol 14α-demethylase) and have been shown in S. cerevisiae to directly interact with and stabilize the binding of fluconazole ( 18 ).…”
Section: Textmentioning
confidence: 99%
“…Fungi contain multiple mechanisms that regulate mutagenesis, including several highlyconserved DNA repair systems, such as double-strand break repair (DSBR), base-excision repair (BER), nucleotide-excision repair (NER), post-replication repair (PRR), and mismatch repair (MMR). DNA polymerases, including several error-prone polymerases, also impinge on mutation rates [90][91][92] . Defects or programmed changes (e.g.…”
Section: Micmentioning
confidence: 99%